Role of perfusion machines in the setting of clinical liver transplantation: A qualitative systematic review. Issue 8 (25th June 2018) - Lai, Quirino; Melandro, Fabio; Rossi, Massimo; Ruberto, Franco; Pugliese, Francesco; Mennini, Gianluca
Abstract: Growing enthusiasm around machine perfusion (MP) in clinical liver transplantation (LT) may be the preamble for standardized practice to expand the donors' pool. The present systematic review investigated all the liver transplantations performed using grafts treated with MP. A systematic review of 309 papers was performed. Eventually, 27 articles were enrolled for the study. A total number of 173 cases were reported. Only 12 cohort studies were identified: the remaining ones were case reports or case series. Hypothermic machine perfusion was performed in 102 (59.0%), normothermic machine perfusion in 65 (37.6%), and controlled oxygenated rewarming in the remaining 6 (3.4%) cases. Donor characteristics, evaluation of graft quality, and endpoints were not homogeneous among the studies. Overall, post‐LT results were excellent, with 1.2 and 4.0% of patients experienced primary non‐function and ischemic‐type biliary lesions, respectively. Conclusion: Until now, no study exists that addresses the role of MP in selecting liver grafts available for LT. All the published studies mainly focused on the feasibility and safety of this new technology. Further research investigating the selection process of marginal donors is required.